Is violence against union members in Colombia : systematic and targeted? (2009)
Violence against union members in Colombia has been at the center of a debate for several years now. Union leaders and NGOs in Colombia and abroad continuously argue that free trade agreements with Colombia should be blocked based on the failure of the current Colombian government to protect union members from targeted killings. We first look at the evolution over time of the indicators for violence against union members and union leaders. In particular we show (using different indicators and data sources) that violence against unionists in Colombia has shown a significant decline over the last seven years. Then, we use available panel data to study the determinants of violence against union members and union leaders. We make special emphasis on testing the claim that a greater intensity in the characteristic activities of unions (such as strikes, wage negotiations, etc.) leads to more violence against union members and union leaders. Using different data sets, data sources and estimation methods, we find no statistical evidence supporting this claim. These results suggest that, on average, violence against unionists in Colombia is neither systematic nor targeted.